A renda da terra na Região Metropolitana da Grande Vitória – ES – Brasil - Cláudio Luiz Zanotelli; Francismar Cunha Ferreira; Larissa Marques de Antônio; Rodrigo Bettim Bergamaschi (Confins)
The text presents preliminary results of a survey in progress on the “land knot” and problematises the appropriation of land rent in the metropolitan region of Grande Vitória in Espírito Santo, Brazil based on Karl Marx and David Harvey. Land concentration, uses and occupancies of the land and empty urban spaces and vacant domiciles are described, contrasting them to housing deficit and programmes for real estate construction and projects for “development” and construction of infrastructure and equipment. The text concludes by discussing the existence of exponential monopoly rents, absolute and differential, in the region. The strategy to achieve these monopoly rents is closely associated with relationships and crossed cooperation between state agents, real estate agents and landowners.